2004
DOI: 10.1093/mutage/geh033
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Tk and Hprt lymphocyte mutants and bone marrow micronuclei in mice treated neonatally with zidovudine and didanosine

Abstract: The nucleoside analog zidovudine (3¢-azido-3¢-deoxythymidine, AZT), by itself or in combination with other antiretroviral drugs, is used perinatally to prevent mother to child transmission of human immunode®ciency virus type 1. AZT is mutagenic in vitro and mutagenic and carcinogenic when administered to neonatal mice. A previous study indicated that the anti-retroviral agent didanosine (2¢,3¢-dideoxyinosine, ddI) potentiated the mutagenicity of AZT in the thymidine kinase (TK) gene of cultured human TK6 lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Recently, increasing emphasis has been placed on examining the effects in infants of transplacental exposures to ZDV due to the increasing number of children born to HIV-infected women who receive ART during pregnancy. For example, experiments in mice have shown that transplacental exposure to ZDV results in an increased frequency of cancer in exposed mice at maturity (NTP, 2006;Olivero et al, 1997), as well as increases in mitochondrial DNA mutations (Chan et al, in press) and elevated mutation frequencies in lymphocytes (von Tungeln et al, 2002(von Tungeln et al, ,2004(von Tungeln et al, ,2007Torres et al, 2007). Furthermore, the incidences of K-ras and p53 mutations were found to be elevated in lung tumors arising in adult mice transplacentally exposed to ZDV, compared with the incidences of these mutations in spontaneous tumors arising in unexposed mice, suggesting that these mutations were the result of chemical-specific events leading to increases in tumor formation later in life (Hong et al, in press).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, increasing emphasis has been placed on examining the effects in infants of transplacental exposures to ZDV due to the increasing number of children born to HIV-infected women who receive ART during pregnancy. For example, experiments in mice have shown that transplacental exposure to ZDV results in an increased frequency of cancer in exposed mice at maturity (NTP, 2006;Olivero et al, 1997), as well as increases in mitochondrial DNA mutations (Chan et al, in press) and elevated mutation frequencies in lymphocytes (von Tungeln et al, 2002(von Tungeln et al, ,2004(von Tungeln et al, ,2007Torres et al, 2007). Furthermore, the incidences of K-ras and p53 mutations were found to be elevated in lung tumors arising in adult mice transplacentally exposed to ZDV, compared with the incidences of these mutations in spontaneous tumors arising in unexposed mice, suggesting that these mutations were the result of chemical-specific events leading to increases in tumor formation later in life (Hong et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…First, DNA incorporation of ZDV and resulting genetic effects may be enhanced by the presence of additional nucleoside analogues such as lamivudine or didanosine (Meng et al, 2002;Bishop et al, 2004;Witt et al, 2004;Meng et al, 2000), although neither of these two nucleosides alone induces micronuclei in mice (Phillips et al, 1991;Von Tungeln et al, 2004;Witt et al, 2004;Von Tungeln et al, 2002;Von Tungeln et al, in press). All women in this study who received ZDV during the prenatal period also received lamivudine, whereas infants received ZDV alone during postpartum treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AZT is incorporated into host cell nuclear and mitochondrial DNA by various DNA polymerases, albeit with much less efficiency than incorporation into proviral DNA by HIV reverse transcriptase [reviewed in , and appears to cause somatic mutations primarily by inducing deletions and perhaps large-scale mutational events leading to LOH in human and mouse cells [Meng et al, 2000a[Meng et al, ,b,c, 2002Mittelstaedt et al, 2004;Von Tungeln et al, 2004. However, AZT also causes point mutations in human cells exposed in culture and in skin and lung neoplasms from in utero exposed mice [Zhang et al, 1998;Meng et al, 2002, Hong et al, 2007.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, ongoing concern regarding the potential long-term consequences to the fetus following NRTI-based prevention of vertical transmission in HIVinfected pregnant women, as many studies have demonstrated that AZT is genotoxic, clastogenic, and mutagenic in cultured cells and mice exposed perinatally or as adults [IARC, 2000;Olivero et al, 1994aOlivero et al, , 1997Dertinger et al, 1996;Von Tungeln et al, 2002Witt et al, 2004;Torres et al, 2007]. The underlying mechanism is presumed to be AZT-DNA incorporation, which has been demonstrated in cultured cells, adult mice, and transplacentally exposed mouse, monkey, and human fetuses [IARC, 2000;Poirier et al, 2004].…”
Section: Introductionmentioning
confidence: 99%